Doenças sexualmente transmissíveis e hepatite C em idosos do município de Botucatu-SP - Andrade, Juliane [UNESP] (2013)
The purpose of this research was to know the epidemiological condition of the elderly in relation to STD/aids and hepatitis C, in Botucatu-SP. It was a quantitative and cross-sectional study. The convenience sample consisted of 382 elderly guests in the waiting room of all health units of the municipality. The interviews were made with items produced by the patient chart and other collection related to sexuality and serology for HIV, syphilis and hepatitis B and C. Most patients were female (61.8%) aged 70 years or older (50.8%). The economically active population was 14.3% and the majority (85.9%) is outside the labor force. Sexual intercourse was reported by 45% of the elderly, 7.1% had eventual partnership, two reported bisexuality and 11.8% reported a history of STDs, gonorrhea being the most cited. The elderly do not have the habit of using condoms and the confidence in the partner was reported as justification (42.7%). One patient had positive HIV serology; ten were diagnosed with syphilis and two patients for hepatitis B and three for hepatitis C. There was significance between sex and STD/aids (p <0.05), and the female has 94.9% of positive tests. There was also significant between STD/aids and sexual activity (p <0.05). There was no association between hepatitis C and these two variables. Due to the significance in univariate analysis, multivariate analysis was performed with logistic regression and the variables lost significance. However that is not possible to say that the number of women had influences in univariate. This study was extremely important, as it enables the provision of serology, which provided knowledge of the diagnosis of STDs/aids and hepatitis C, allowing the treatment and consequently improving the quality of life. The results of this study possibly changes the look of health professionals to the vulnerability of the elderly against STDs/aids and hepatitis C, and also leads managers to promote ...